A SUSPENSÃO DE SEGURANÇA NA CONTRAMÃO DOS DIREITOS DOS POVOS INDÍGENAS NO BRASIL - Belém, Breno de Campos (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2022)
Indigenous peoples, in addition to the right to self-determination provided for in the Brazilian Federal Constitution of 1988, have international treaties to protect this right, of their identities, cultures and ways of living. However, their rights and existence are constantly violated by enterprises and large capitalist projects to occupy their territorial space and nature exploration. In this work, a reflection is made on the violation of this right, specifically through the legal mechanism called security suspension. We will point out one of the cases in which this judicial measure was taken until the end of Belo Monte hydroelectric construction. With the completion of the power plant, it is clear that the country’s executive and judiciary powers, through this mechanism, take arbitrary decisions that suit them best, regardless of which and how many lives are and will be involved in the course of these projects.